COMPARISON OF CHILDHOOD AND CURRENT RESIDENTIAL LOCATION SATISFACTION AFTER RELOCATION OR STAYING - Sisan, Wahid Ramadhan; Kusuma, Hanson Endra (Journal of Architecture&ENVIRONMENT, 2025)
This study is based on the premise that residential satisfaction in adulthood may be influenced by satisfaction with childhood residential locations. Residential location is not only a physical setting but also part of the interactive process that shapes an individual's relationship with their environment through sensory experience, memory, and perception. Data were collected through open-ended questionnaires distributed to adult respondents from various demographic and geographic backgrounds. The responses were qualitatively analyzed using open coding, axial coding, and selective coding methods. The results revealed a significant correlation between satisfaction with childhood residential locations and satisfaction with current residences after relocation or staying, including housing location choices. These findings provide valuable insights for urban planners in designing residential environments that accommodate the diverse preferences of the community. Furthermore, this study emphasizes the importance of considering childhood experiences in understanding future housing location needs.